Development of Energy Management Information System (EMIS) for energy-saving awareness - Enche Shaari, Dayana Khadijah; Abu Hanifah, Mohd Shahrin (Institute of Electrical and Electronics Engineers Inc., 2023)
Anticipated surge in electricity expenses within the confines of the International Islamic University of Malaysia (IIUM) campus stems from the pervasive absence of energy conservation consciousness among the IIUM community. On account of the rise of energy consumption, energy wastage happens, resulting in emission of greenhouse gas and carbon that harms the environment. An Energy Management System (EMS) under the control of IIUM Development Division does exist. However, this system is exclusively accessible to the said division, and the data it encompasses is intricate in nature. Hence, the primary objective of this project is to construct an Energy Management Information System (EMIS) with the aim of fostering energy-saving awareness among the IIUM Community, specifically emphasizing the Kulliyyah of Engineering (KOE), through the dissemination of pertinent information via the system. Based on the EMIS (Energy Management Information System) developed specifically for this project, it can be inferred that there is a notable enhancement in the level of energy-saving consciousness within the IIUM community in KOE as indicated by the conducted survey.